Analisis Sandcone Test (AASHTO T 191 dan ASTM D 1556 64) Pada Peningkatan Jalan Jepara – Kedungmalang – Pecangaan - Yayan Adi Saputro; Khotibul Umam; Shiska Fauziah (Universitas Tidar, 2020)
Concrete road works on the improvement of the Jepara - Kedungmalang - Pecangaan road are the activities of the Publick Works Department of Highways in Central Java Province. Quality control in a building structure work is very important to support the strength of the structure. In planning the road structure, it is necessary to have density of soil and foundation layers that meet the requirements. To get the value of the degree of density that is from the sandcone test where in the sandcone test there are several standart methods or references for example from AASHTO T 191 and ASTM D 1556 - 64. In this study the aims is to obtain the value of the degree of density, how big is the difference between the AASHTO T 191 standart and ASTM D 1556 - 64, and know the water content. From the test result, the optimum moisture content value is 6.5%, dry density is 2.17gr/cm3, the value of the degree of density mostly ranges from